2015
DOI: 10.1111/jzs.12114
|View full text |Cite
|
Sign up to set email alerts
|

The parthenogenetic Marmorkrebs (Malacostraca: Decapoda: Cambaridae) is a triploid organism

Abstract: There is a close association between parthenogenesis and polyploidy. For this reason, we undertook a karyological analysis to test whether the parthenogenetic Marmorkrebs, Procambarus fallax forma virginalis, possesses an enlarged set of chromosomes. For this purpose, we karyotyped the Marmorkrebs, the sexual form of P. fallax (together called P. fallax complex), and the closely related species P. alleni. The latter shows 94 chromosomes in the haploid condition. In contrast to this, we found a haploid set of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 67 publications
(141 reference statements)
3
47
0
3
Order By: Relevance
“…In control, the cross sectional area segments of hepatopancreas reached 31332.11±1189.72 µm 2 , while the slices in the experiment were more than 42.3 % -4475.77±42147.38 µm 2 . The value of the tubule rift did not differ significantly -in the control area of the rift of the tubular reached 6301.07±409.37 µm 2 , in the experiment -6868.51±652.33 µm 2 . This means that the increase in the size of the lobules of hepatopancreas occurred due to tissue proliferation and accumulation of fat inclusions in these tissues.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In control, the cross sectional area segments of hepatopancreas reached 31332.11±1189.72 µm 2 , while the slices in the experiment were more than 42.3 % -4475.77±42147.38 µm 2 . The value of the tubule rift did not differ significantly -in the control area of the rift of the tubular reached 6301.07±409.37 µm 2 , in the experiment -6868.51±652.33 µm 2 . This means that the increase in the size of the lobules of hepatopancreas occurred due to tissue proliferation and accumulation of fat inclusions in these tissues.…”
Section: Discussionmentioning
confidence: 94%
“…In the control, area of the cross-section slices of lobules of hepatopancreas reached 31332.11±1189.72 µm 2 , while in the experiment segments were 42.3 % (p <0.05) bigger -42147.38±4475.77 µm 2 (Fig. 3).…”
Section: International Letters Of Natural Sciences Vol 56mentioning
confidence: 99%
See 2 more Smart Citations
“…The observed increase in a number of acuminate and pappose setae of putative mechanoreceptive function (Hobbs, 1972; around the gonopores and the annulus during maturation had not been described before in decapods (Vogt et al, 2004). Martin et al (2015) recently showed that the marbled crayfish is a triploid, showing a triple amount of the haploid number of chromosomes. In addition, they detected a huge amount of a subtelocentric chromosome which became clear firstly in haploid and secondly in diploid cells of sexual individuals of the P. fallax complex.…”
Section: Parthenogenesismentioning
confidence: 99%